A Novel Neuro-Fuzzy Controller for Multilevel Renewable Energy System - T PAVAN KUMAR; B N KARTHEEK (Institute of Advanced Engineering and Science, 2015)
Recently, Development and the utilization of single phase based multilevel inverters has been increased. This paper proposes concept based new topology based seven level inverter with less number of power electronics switches with utility grid connection. This proposed multilevel inverter operates with only eight power electronics switches at their fundamental frequency. This inverter produces seven level output from the input here we considered as a photovoltaic system. The cost, complexity, switching losses are small due to because of usage of less number of switches. The DC/DC converter receives input from which the three positive output voltages are generated and the multilevel inverter performs as a polarity reversal that provides both the positive and negative cycle output. For further enhancement in the output waveform, the filter circuit can be integrated in the output terminal of the multilevel inverter. This paper also proposed a concept of a neuro-fuzzy controller for controlling the seven level inverter. The simulation results are observed by means of MATLAB simulink toolbox.